Training & development, career development, and organizational commitment as the predictor of work performance - Hosen, Sharif; Hamzah, Siti Raba'ah; Arif Ismail, Ismi; Noormi Alias, Siti; Faiq Abd Aziz, Mohd; Rahman, Md Mizanur (Elsevier, 2024)
This study aims to justify the mediating effect of organizational commitment in the association between training and development, career development, and work performance. Data was collected from 362 frontline hotel employees through a survey by random sampling technique. The analysis methodology comprises descriptive statistics, measurement, and structure models through SPSS 23 and Smarts PLS 3.0. This study significantly examined the correlation between training and development and work performance, career development, and work performance. Moreover, organizational commitment in the hotel sector is significantly associated with work performance. Furthermore, the significant correlation between training and development and work performance career development among hotel personnel is mediated by organizational commitment. Owners and managers should know the necessary policies to enhance employees' work performance and organizational commitment and consider appropriate behaviour. Besides, all required facilities for enhancing career development and training and development should be implemented to strengthen hotels' present and future demands. It is furthered by the study's explanations of the results and their limitations, which also included suggestions for future research possibilities. This research filled the gap in the hotel industry in Bangladesh, where study works into wide-ranging training and development, career development practices, organizational commitment, and work performance were rare.